Marking a Quiet Community: Analyzing Narratives of Community Reentry Among Filipino Plea Bargainers - Canoy, Nico A (Archīum Ateneo, 2021)
Since President Rodrigo Duterte launched his war on drugs campaign in 2016; there has been a growing scholarship documenting the empirical analyses of the policy's drug-related harms. Eighteen Filipino plea bargainers were interviewed and asked to narrate their experiences of eventually returning back to the community after release. Their stories were analyzed using Stephens and Breheny's (2013) integrated approach to narrative analysis. Three broader categories were evident that evoke the interplay between wider systemic conditions and one's exercise of restricted agency. Under first broader category of reentering a spatially marked and quiet community; four personal narratives are evident; namely: I don't want to go out anymore; I just keep away from that place; I don't see them anymore; and I'm living in a dead town. Under the second broader category of my family upon reentering the community; two personal narratives are evident: I felt ashamed and Where are you going? Don't use anymore. Under the third broader category of reentering the community without work; three personal narratives are evident: I could not give anything to my children; I did all the work at home; and I'm looking for work; but. Our findings contribute to the examination of interlocking systemic conditions surrounding the accounts of those incarcerated in local police crackdowns. In this context; there is a strong need to respond to the challenges of rebuilding community processes (e.g.; permanently delisted from the community drug watchlist) and strengthening employment opportunities in partnership with the local government.